(untitled) (Current Horticulture, 2024)
India has a rich and varied heritage of biodiversity, encompassing a wide spectrum of habitats from tropical rain forests to alpine vegetation and from temperate forests to coastal wetlands. Out of 18 biodiversity hot spots identified in the world, four hotspots, i.e. The Western Ghats, Eastern Himalaya, Western Himalaya, and Nicobar islands are in India. Besides, India has 26 recognized endemic centres which are home to one-third of all the flowering plants identified and described so far. There are 8.7 million species of the world’s biota. Of them, only 1.7 million have been described to date, and their distribution is highly uneven. About 7% of the world’s total land area is home to half of the world’s species, with the tropics alone, accounting for 5 million. India contributes significantly to the biodiversity of the world, accounting 7.31 % of the global plant diversity from 2.4% of the world’s area.